PENERAPAN MODEL PEMBELAJARAN AKTIF, INOVATIF, KREATIF, EFEKTIF DAN MENYENANGKAN (PAIKEM) UNTUK MENINGKATKAN HASIL BELAJAR IPS SISWA KELAS IV SD MUHAMMADIYAH 6 PEKANBARU (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract : This research was conducted because of the result of learning science study class IV SD Muhammadiyah 6 Pekanabru. KKM set school, namely: 76. From 23 people students, at KKM only 6 students (26,08 %), while students who has not reached KKM is 17 people students (73,91%) worth of the average class 62,60. The purpose of this research to improve learning outcomes IPS class IV SD Muhammadiyah 6 Pekanbaru with the application of learning models active, innovative, creative, effective and fun (PAIKEM). The results of the study obtained the average score a score basic 62,60 increase in cycle I of 23,27% to 77,17. In cycle II student average score also increased by 32,30% to 82,82. On the score basic Classical mastery learn social class the students were 26,08% (not finished). Afterwards applied learning model active, innovative, creative, effective and exciting (PAIKEM) in cycle I Classical mastery student learning increase by Classical mastery 43,47% and in cycle II Classical mastery learn students are very better with Classical mastery 82,60% activity teachers in the first meeting of cycle I the percentage is 62,50% to a category good. The second increased to 70,83% to a category good. In the first meeting of cycle II activity teachers increased to 83,34% to a category is very good. In the second increased to 95,84% to a category is very good. Activity students in the first meeting of cycle I the percentage is 54,16% to a category enough. The second increased to 75% to a category good. In the first meeting of cycle II activity students increased to 87,50% to a category is very good. In the second increased to 91,66% to a category is very good.Key Words : PAIKEM, learning outcomes IPS